Poor Outcome of Bilateral Lower Extremity Morel-Lavallee Lesions: A Case Report - Stanley, Sharon S.; Molmenti, Ernesto P.; Siskind, Eric; Kasabian, Armen K.; Huang, Su-I D. (International Journal of Angiology, 2014)
The Morel-Lavallee lesion is a closed, internal degloving injury that results when a strong, shearing force is applied parallel to the plane of injury, as is common in vehicular trauma. It is an underdiagnosed entity that is often missed during the initial trauma workup as symptoms can be subtle. There are few reports of lesions occurring below the knee. Most cases affect the proximal thigh and trochanter, as these tend to be dependent areas in high velocity trauma. To the best of our knowledge, this is the first literature report of bilateral lower extremity Morel-Lavallee lesions.
Keywords: Morel-Lavallee lesion; internal degloving injury; skin necrosis; skin graft; amputation; trauma